A cadeia produtiva do leite em Nossa Senhora da Glória/SE: desafios e transformação no sistema produtivo dos pequenos agricultores familiares - Gois, Laisa de Souza (2024)
The municipality of Nossa Senhora da Glória/SE has a developed dairy production chain and has been consolidated as a dairy hub as a system. One of the social actors responsible for the development of this activity is the small family farmers who articulate with the different local actors. From this activity, many transformations have occurred in the marketing channels conditioned by the requirements of an oligopolized market in which the dairy agro-industries determine the conditions for the insertion of farmers in the production chain. In view of this, this study aimed to analyze the scopes, limits and possibilities of family farmers in the milk production chain in the municipality of Nossa Senhora da Glória/SE. To achieve the objectives, several methodological procedures were used with the use of the empirical-analytical method, the survey and bibliographic review, field activities and application of the semi-structured questionnaire ICV (Life Condition Index) used to measure what are the socioeconomic effects of milk production and by the dimension of development as overcoming the deprivations of freedom, and that this was demonstrated in the study, the socioeconomic potential of this activity, even with its internal contradictions. Thus, the study of the milk production chain can be analyzed according to the potential of organization and socioeconomic contribution to family farmers who, even in the face of the demands and difficulties in the insertion of technologies in production, they have resisted and contributed to the advancement of the production chain of the municipality.